If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1d + 3 = 18 + -2d Reorder the terms: 3 + 1d = 18 + -2d Solving 3 + 1d = 18 + -2d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '2d' to each side of the equation. 3 + 1d + 2d = 18 + -2d + 2d Combine like terms: 1d + 2d = 3d 3 + 3d = 18 + -2d + 2d Combine like terms: -2d + 2d = 0 3 + 3d = 18 + 0 3 + 3d = 18 Add '-3' to each side of the equation. 3 + -3 + 3d = 18 + -3 Combine like terms: 3 + -3 = 0 0 + 3d = 18 + -3 3d = 18 + -3 Combine like terms: 18 + -3 = 15 3d = 15 Divide each side by '3'. d = 5 Simplifying d = 5
| 2x+3(-x+4)=16 | | 5s+6t=60 | | x^3-3x=28 | | h^2-16h=0 | | y^3+y^2+10=0 | | -16t+135t+76=0 | | 6(t-1)=2(2t-4) | | x-27=8 | | 7p+12q=83 | | 6(8-a)=36 | | 4x+10y=76 | | -7(v+1)=3v-7+2(2v+8) | | 9x+3(33-4x)=78 | | 38=-2w+4(w+6) | | -16t(2+t)=0 | | 5-3(x-4)=15 | | 27z^2-46z=0 | | (X+3)(x-15)= | | 7v+3=-8(v+9) | | (X-3)(x+15)= | | j^2+22j=0 | | (X-3)(x-15)= | | (X-15)(x-3)= | | (x+40)(x)=6000 | | (X+15)(x-3)= | | -8x+6(x+3)=36 | | (X+15)(x+3)= | | 3d+5=5d-7 | | x^4-2x^2-45=0 | | 2x^2+7a+6=0 | | -2w+19=5(w+8) | | m^2+10m-11=0 |